ANALYSIS ON STUDENTS' HOTS THROUGH EXTENSIVE READING IN ENGLISH DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH PONOROGO - Indriastuti, Niken Reti; Mustikawati, Diyah Atiek; Asiyah, Siti (Premise: Journal of English Education and Applied Linguistics, 2023)
This research investigates students' higher-order thinking skills in the English Department of Universitas Muhammadiyah Ponorogo while learning reading through extensive reading (ER) approach. The class discussion in a chatting group (WhatsApp) was chosen since the learning process was conducted online; the data was chatting texts of class discussion when the intermediate and advanced reading class students presented their selected material. There were sixteen texts presented in the intermediate reading class. The texts could generate one hundred and six questions, one hundred and six answers, and twelve texts presented in the advanced class, creating seventy-seven questions and sixty-eight answers. The questions and answers were then analyzed based on the top three levels of Bloom's cognitive taxonomy. The results show that all questions could present their skill of higher thinking order. Meanwhile, most of the answers could reflect HOTS too, although there were few considered as LOTS (low-order thinking skill).